Performance and emissions of Chlorella vulgaris with ruthenium oxide in CI engines. (15th April 2022) - Arunprasad, J.; Thirugnanasambantham, R.; Elango, T.; Pachiannan, Tamilselvan; Thangaraj, Satheeswaran; Basha, Sakeenabi; Brindhadevi, Kathirvel
Highlights: Biodiesel is made from C. vulgaris oil, which is used as a feedstock. Lowest BSFC and maximum BTE obtained for B20 + 100 ppm RuO2 blend. The B20 + 100 ppm RuO2 combination generated less CO, HC, and smoke. The ASTM standards were used to measure the fuel characteristics. Abstract: Nano additives have been applied to biodiesel blends to increase their efficiency by improving fuel properties. The present study was carried out using biodiesel blends of Chlorella vulgaris methyl ester and RuO2 nano additions to analyze the performance and emissions of a single-cylinder diesel engine. The test was carried out using B20, B20 + 50 ppm of RuO2, B20 + 100 ppm of RuO2 fuel samples at various load conditions on a diesel engine. The fuel properties for all the samples were found out using standard methods. The performance and emission characteristics of the engine were studied to assess fuel blends with and without additives. The experiment's results indicated that B20 + 100 ppm of RuO2 improves the brake thermal efficiency compared to B20. The nano additives blended fuel emissions were considerably lower than the B20 fuel emissions, while the minimum amount of NOx increased than the B20 fuel. Results exhibited that adding B20 + 100 ppm of RuO2 to C. vulgaris methyl ester improved engine performance and decreased the exhaust pollutants.